STRATEGI PUBLIC RELATIONS PT. PELNI (Persero) MENGIMPLEMENTASI PROGRAM CSR MELALUI PROGRAM KEMITRAAN DAN BINA LINGKUNGAN - Intani, Retno (Universitas Prof. Dr. Moestopo (Beragama), 2018)
This research describes the effort of PT Pelni (Persero)’s Public Relations (PR) to provide Corporate Social Responsibility (CSR) through Program Kemitraan Dan Bina Lingkungan (PKBL). CSR is a part of community relations activity, which happens to be part of PR function to build positive images of the company. The concepts that used to understand the phenomenon under the study are organization communications, Public Relations, strategic management of Public Relations, interactionist symbolic, partnership and CSR through qualitative case study considered as the right method to provide a holistic preview about strategic management of PR for CSR implementation. The findings of the research show that organization communications if implemented well, precisely and interactivy will accelerate Public Relations strategy for CSR implementation through PKBL although PKBL is structured under controlling by Finance Department PT Pelni (Persero) cq Treasury division not restrained by Corporate Secretary PT Pelni (Persero) in which PR and CSR fields are managed. CSR known as a PR activity that contributes to build and maintain good relationship between company and stakeholders and also to enhance positive images of the company.